Atraumatic Intercostal and Intrathoracic Liver Herniation Related to Influenza A. Issue 7 (23rd July 2020) - Harne, Prateek S.; Mukherjee, Samiran; Shepherd, Zachary
ABSTRACT: Nontraumatic and spontaneous intercostal and intrathoracic herniations are defined as protrusions of intra-abdominal contents through acquired or congenital defects of the abdominal and thoracic walls without any proceeding trauma and are sparsely reported in the literature with less than 35 detailed case reports reported in the literature worldwide. Most of these cases result from abdominal trauma and are considered surgical emergencies. The content of these herniations, as reported in the literature, have classically been lungs and intra-abdominal organs. We report a case of nontraumatic intercostal and intrathoracic liver herniation, which was managed conservatively given minimal liver injury and rapidly improving symptoms.